A preliminary inventory of rock glaciers at 30°S latitude, Cordillera Frontal of San Juan, Argentina - Esper Angillieri, María Yanina (2009)
The Dry Andes of the Cordillera Frontal of San Juan (301S latitude) is characterized by high relief with peaks up to 5000ma.s.l. This geological province is mainly made up of a suite of Triassic to Miocene volcanic rocks. Modern ice glaciers are small and few in number, and persistent snow .elds are similarly small and scattered. The predominant landforms in these areas have been shaped in a periglacial environment superimposed on an earlier glacial landscape. A preliminary inventory map of rock glaciers was constructed using optical remote sensing techniques, digital topographic analysis and aerial photograph data organized in a geographic information system (GIS). Over 140 rock glaciers have been identi.ed: 90% are active or inactive and the rest are fossil. A total of 88 rock glaciers are considered active. The most common periglacial features recognized in the area are talus glaciers, and only 23% are tongue-shaped glaciers.